3D amorphous NiFe LDH nanosheets electrodeposited on in situ grown NiCoP@NC on nickel foam for remarkably enhanced OER electrocatalytic performance. Issue 15 (30th March 2020) - Nie, Jianhang; Hong, Min; Zhang, Xiaohua; Huang, Junlin; Meng, Qin; Du, Cuicui; Chen, Jinhua
Abstract : 3D amorphous NiFe LDH nanosheets electrodeposited on hierarchical porous and conductive NiCoP@NC/NF in situ grown on nickel foam exhibited outstanding OER catalytic activity and stability. Abstract : NiFe LDH (layered double hydroxide) is currently attracting increasing attention as a type of promising electrocatalyst for oxygen evolution reaction (OERs); however, the biggest obstacle to its large-scale practical application is its poor conductivity and limited active sites. Herein, we report a three-dimensional NiFe LDH with high conductivity and dense active sites, where amorphous NiFe LDH nanosheets are directly electrodeposited on the surface of a hierarchical porous NiCoP@NC derived from the calcination and phosphorization of metal–organic frameworks (ZIF-67) in situ grown on nickel foam. Based on the 3D porous structure, abundant exposed active sites, fast electron and mass transfer rates and strong synergetic effects between NiCoP@NC and NiFe LDH, the resultant NiFe LDH/NiCoP@NC/NF catalysts exhibited significantly enhanced OER catalytic performances compared with NiFe LDH on nickel foam and most of the reported NiFe LDH-based catalysts: a low overpotential of 210 mV for yielding a current density of 10 mA cm −2, an extremely small Tafel slope (35 mV dec −1 ) and excellent durability. For overall water splitting, with NiFe LDH/NiCoP@NC/NF as the anode and NiCoP@NC/NF as the cathode, the assembled two-electrode system only required 1.54 V to obtain a stable current density of 10 mA cm −2 in 1 M KOH for at least 40 h. This research provided a simple and facile way to develop non-noble-metal oxygen evolution catalysts for replacing high-cost noble metal catalysts.